2014
DOI: 10.1177/0954405414532628
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and analysis of isothermal forging of AA6063 obtained from material processed by equal channel angular pressing severe plastic deformation

Abstract: In this research study, a comparative examination on the mechanical properties of AA6063 has been carried out after having been processed by isothermal forging, using plane-shape dies and starting from different initial deformation states. It introduces the novelty of employing experimental data obtained from the isothermal forging so as to model the flow rules of AA6063 processed by equal channel angular pressing taking temperature into account and using artificial neural networks to this end. Subsequently, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…To improve the strength of the aluminum, alloying and age-hardening were used as the main strengthening mechanisms. 1,2 In recent years, severe plastic deformation (SPD) processes such as equal channel angular pressing (ECAP) 3,4 and accumulative roll-bonding (ARB) 5 are used for improving the mechanical and functional properties of aluminum alloys. 6,7 In these processes, ultra-large plastic strain is introduced into a bulk metal in order to create ultra-fine grained metals.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the strength of the aluminum, alloying and age-hardening were used as the main strengthening mechanisms. 1,2 In recent years, severe plastic deformation (SPD) processes such as equal channel angular pressing (ECAP) 3,4 and accumulative roll-bonding (ARB) 5 are used for improving the mechanical and functional properties of aluminum alloys. 6,7 In these processes, ultra-large plastic strain is introduced into a bulk metal in order to create ultra-fine grained metals.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21] So far, various SPD methods have been proposed for SPD that let a specimen plastically deformed with no considerable alteration in size and shape. 21,22 Two of the most successful are high-pressure torsion (HPT) and equal channel angular pressing (ECAP). 13,23 Other methods include multi-directional forging, 19 accumulative roll bonding, 24 equal channel forward extrusion, 12 constrained groove pressing, 25 twist extrusion, 26 planar twist channel angular extrusion, 27 etc.…”
Section: Introductionmentioning
confidence: 99%
“…5,6,11 Using ultrafine-grained (UFG) materials can be considered as an alternative method of increasing both the mechanical properties and corrosion resistance of metallic materials such as aluminum and magnesium, which can be perfectly achieved by severe plastic deformation (SPD) techniques. 1217 Recent studies revealed that mechanical properties of Mg alloy could be significantly improved by different SPD processes. 1820 For example, Faraji et al 21 manufactured a UFG tube of AZ91 by tubular channel angular pressing (TCAP) and produced UFG bulk of AZ91 by accumulative back extrusion (ABE) 22 which resulted in superior mechanical and microstructural properties.…”
Section: Introductionmentioning
confidence: 99%